Quick method for isolating RNA from raw and ripe fleshy fruits as well as for co-isolating DNA and RNA from polysaccharide- and polyphenol-rich leaf tissues - Pandit, Sagar Subhash; Mitra, Sirsha Sribas; Giri, Ashok P.; Gupta, Vidya Shrikant (Journal of Plant Biology, 2007)
Qualitative and quantitative changes in its chemical composition make it difficult to use any single procedure for isolating good-quality RNA from fruits at various ripening stages. Although the CTAB method has eliminated some specific problems, e.g., low pH in raw fruit or high levels of polysaccharides, oligosaccharides and phenolics in raw and ripe fruits, the total time required is long and unsuitable for high throughput. Here, we successfully modified this CTAB protocol to isolate good-quality RNA from (i) fleshy fruits, especially raw and ripe mangos; (ii) the leaves of a succulent air plant; and (iii) an oligosaccharide-rich onion epidermis. This RNA proved useful for downstream transcriptomic applications, where RT-PCR followed by RACE yielded the complete open reading frame of the (mango) terpene synthase gene. We also extended the utility of this protocol to co-isolate good-quality genomic DNA from the supernatant that remained after RNA precipitation. This preparation was useful for the arbitrary primer multilocus amplification of genomic DNA as well as for single locus diversity marker amplifications of the ctDNA and mtDNA.
Keywords: DNA-RNA co-isolation; fleshy fruit; Mango; oligosaccharide-rich; Ripening; transcriptomic studies

Global transcriptome analysis of grapevine ( Vitis vinifera L.) leaves under salt stress reveals differential response at early and late stages of stress in table grape cv. Thompson Seedless - Upadhyay, Anuradha; Gaonkar, Tulsi; Upadhyay, Ajay Kumar; Jogaiah, Satisha; Shinde, Manisha P.; Kadoo, Narendra; Gupta, Vidya Shrikant (Plant Physiology and Biochemistry, 2018)
Among the different abiotic stresses, salt stress has a significant effect on the growth and yield of grapevine (Vitis vinifera L.). In this study, we employed RNA sequence based transcriptome analysis to study salinity stress response in grape variety Thompson Seedless. Salt stress adversely affected the growth related and physiological parameters and the effect on physiological parameters was significant within 10 days of stress imposition. A total of 343 genes were differentially expressed in response to salt stress. Among the differentially expressed genes (DEGs) only 42 genes were common at early and late stages of stress. The gene enrichment analysis revealed that GO terms related to transcription factors were over-represented. Among the DEGs, 52 were transcription factors belonging to WRKY, EREB, MYB, NAC and bHLH families. Salt stress significantly affected several pathways like metabolic pathways, biosynthesis of secondary metabolites, membrane transport development related pathways etc. 343 DEGs were distributed on all the 19 chromosomes, however clustered regions of DEGs were present on chromosomes 2, 5, 6 and 12 suggesting probable QTLs for imparting tolerance to salt and other abiotic stresses. Real-time PCR of selected genes in control and treated samples of grafted and own root vines demonstrated that rootstock influenced expression of salt stress responsive genes. Microsatellite regions were identified in ten selected salt responsive genes and highly polymorphic markers were identified using fifteen grape genotypes. This information will be useful for the identification of key genes involved in salt stress tolerance in grape. The identified DEGs could also be useful for genome wide analysis for the identification of polymorphic markers for their subsequent use in molecular breeding for developing salt tolerant grape genotypes.

Importance of conserving fragmented forest patches with high diversity of flowering plants in the northern Western Ghats: an example from Maharashtra, India - Kasodekar, Amol; Jadhav, Amol Dilip; Bhagat, Rani; Pawar, Rakesh Mahadev; Gupta, Vidya Shrikant; Kadoo, Narendra (Journal of Threatened Taxa, 2019)
The northern Western Ghats (NWG) comprises of a patchy continuum of forests that have been severely fragmented mainly due to anthropogenic activities. We documented tree diversity within a representative fragmented forest patch of the NWG to study the effects of fragmentation on forest structure and composition. The floristic survey was conducted by replicated strip transect sampling method leading to a total sampling area of 0.3ha. A total of 444 individual trees (Girth>10cm) were sampled, which represented 49 tree species belonging to 42 genera and 23 families. Species richness per unit area and tree density were higher than previously reported values from similar forest type in various regions of NWG. These variations, however, could have resulted due to differences in the sampling area, sampling method, and girth classes used across different studies. Nevertheless, various diversity parameters such as N/S ratio, Simpson’s index, Shannon’s index, and Fisher’s α index were comparable with those reported in previous studies in the Western Ghats. The observed species richness was close to species richness estimates such as abundance-based coverage estimate, Chao-1, and Jackknife estimators. The present study also enumerates 108 species of understory flowering plants, which is provided as a checklist. While access restrictions are imposed in protected areas having high conservation priority, such restrictions are not imposed in non-protected areas, which make them much more vulnerable to anthropogenic activities. Hence, this study recommends that owing to their high diversity, the fragmented forest patches of NWG should also be given high conservation priority.